2005
DOI: 10.4161/hv.1.2.1651
|View full text |Cite
|
Sign up to set email alerts
|

Characterisation of the Protein Content of a Meningococcal Outer Membrane Vesicle Vaccine by Polyacrylamide Gel Electrophoresis and Mass Spectrometry

Abstract: Previously published online as a Human Vaccines ACKNOWLEDGEMENTSWe wish to thank Philipp Oster for critical reading of the manuscript. Research Paper Characterization of the Protein Content of a Meningococcal Outer Membrane Vesicle Vaccine by Polyacrylamide Gel Electrophoresis and Mass Spectrometry ABSTRACTThe development and evaluation of outer membrane vesicles as vaccines against meningococcal disease has been carried out for more than two decades. Although such vaccines have limitations and are not widely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2006
2006
2010
2010

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 39 publications
(29 citation statements)
references
References 15 publications
1
28
0
Order By: Relevance
“…Antibodies to NspA were determined with OMVs from E. coli cells that expressed or that did not express rNspA. Although MeNZB contained a distinct amount of NspA protein, as previously shown on Coomassie blue-stained polyacrylamide gels (24,56) and as probed in our study with a specific antibody on immunoblots, most vaccinees showed no increase in IgG to this protein, nor was there any significant difference in the responses between the two vaccine groups (data not shown). MenBvac contained only trace amounts of this antigen.…”
Section: Igg Antibody Responses To Omvs and Live Meningococcimentioning
confidence: 97%
“…Antibodies to NspA were determined with OMVs from E. coli cells that expressed or that did not express rNspA. Although MeNZB contained a distinct amount of NspA protein, as previously shown on Coomassie blue-stained polyacrylamide gels (24,56) and as probed in our study with a specific antibody on immunoblots, most vaccinees showed no increase in IgG to this protein, nor was there any significant difference in the responses between the two vaccine groups (data not shown). MenBvac contained only trace amounts of this antigen.…”
Section: Igg Antibody Responses To Omvs and Live Meningococcimentioning
confidence: 97%
“…The second ABC transporter, NMB0634 (FbpA), is a virulence factor with a role in iron uptake (42); however, the role for the third ABC transporter, NMB1612, is unknown despite its presence in OMV and OM preparations (59). The other hypothetical protein associated with the periplasm, NMB0928, has been reported to be present as a constituent of OMV derived from N. meningitidis (52,53,55,59) and N. lactamica (53) and also to be conserved across many meningococcal serogroups and capable of inducing murine bactericidal antibodies (8). The thiol-disulfide interchange protein DsbC is potentially interesting as a vaccine candidate due to function, as it catalyzes the formation of disulfide bonds essential for the conformational stability and folding of proteins, and recently, the DsbC-encoding open reading frame has been reported to become upregulated in meningococci during infection of HeLa cells (47).…”
Section: Discussionmentioning
confidence: 99%
“…The pellet was resuspended in 100 l of SDS-PAGE sample buffer (50 mM Tris-HCl (pH 6.8), 2% SDS, 100 M 2-ME, 10% glycerol, 0.1% bromophenol blue). Outer membrane vesicles (OMVs) were prepared as described previously (35). Proteins were separated under reducing conditions by SDS-12% PAGE, then the proteins transferred to polyvinylidene difluoride membranes (Millipore).…”
Section: Far Western Blot Analysismentioning
confidence: 99%